Heparin-Related Thrombocytopenia Triggered by Severe Status of Systemic Lupus Erythematosus and Bacterial Infection. (6th September 2016) - Suzuki, Satoshi; Nakajima, Shihoko; Ando, Taiki; Oda, Keisuke; Sugita, Manabu; Maeda, Kunimi; Nakiri, Yutaka; Takasaki, Yoshinari
Abstract : A patient with severe lupus nephritis developed thrombocytopenia during treatment with high-dose steroids. In addition to viral- or disease-induced cytopenia, the pathology was believed to arise from diverse contributing factors, such as thrombotic microangiopathy and heparin-related thrombocytopenia (HIT). By combining plasma exchange therapy and intravenous cyclophosphamide, we successfully controlled the SLE activity and improved the thrombocytopenia. An antecedent bacterial infection or SLE activity is believed to have contributed to the concurrent HIT.